Deception jamming against doppler beam sharpening radars - Frazer, Gareth; Balleri, Alessio; Jacob, George S. (IEEE, 2019)
Missile seekers are becoming increasingly more capable of using Doppler Beam Sharpening (DBS) modes as part of the homing cycle. This paper develops jamming theory and uses it for practical implementation of inserting false targets into a DBS image. The theory is also developed for how incorrect estimations of the seeker trajectory can affect the quality and location of the false target. The simulated and experimental results show how received missile seeker waveforms can be modified to create false targets at desired locations.
Keywords: Jamming; Missiles; Satellite broadcasting; Doppler effect; Trajectory; Doppler radar